2022
DOI: 10.1111/jen.12997
|View full text |Cite
|
Sign up to set email alerts
|

Volatile organic compounds released by wheat as a result of striped shieldbug feeding and insect behaviour

Abstract: The most popular plant protection method is chemical; however, this is often connected with repeated treatments. Therefore, eco‐friendly strategies need to be investigated. A good alternative is to use the natural repellent properties of plants. The aims of this study were to determine how adult striped shieldbugs (Aelia acuminata L.) feeding on spring wheat plants affect the emission of volatile organic compounds (VOCs) and to determine the reaction of these insects to synthetic blends of VOCs. Using GC/MS fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 78 publications
0
3
1
Order By: Relevance
“…In our study, calcium treatment led to changes in the content of several compounds, among them, the percentages of (E)-2-hexen-1-ol and 1-octen-3-ol were significantly decreased, while the percentages of β-lonone and (E,E)-2,4-hexadienal were significantly increased. In other studies, (E)-2-hexen-1-ol and 1-octen-3-ol have been identified as pest HIPVs, and their increased emissions attract natural enemies of herbivores [69,70]. This finding was contradictory to that of the present study.…”
Section: Discussioncontrasting
confidence: 99%
“…In our study, calcium treatment led to changes in the content of several compounds, among them, the percentages of (E)-2-hexen-1-ol and 1-octen-3-ol were significantly decreased, while the percentages of β-lonone and (E,E)-2,4-hexadienal were significantly increased. In other studies, (E)-2-hexen-1-ol and 1-octen-3-ol have been identified as pest HIPVs, and their increased emissions attract natural enemies of herbivores [69,70]. This finding was contradictory to that of the present study.…”
Section: Discussioncontrasting
confidence: 99%
“…This result may be a confirmation of Pare and Tumlinson's [20] suggestion that the conversion of C 6 compounds into an acetate form is promoted while crossing the undamaged plant tissue barrier. Moreover, using GC/MS, Sendel et al [21] found that Aelia acuminata L. (1 or 2 adult pairs) significantly induced VOC emissions from wheat plants, where, as a result of biotic stress, larger amounts of the following VOCs were released: (Z)-3-hexenal, (E)-2-hexenal, (Z)-3-hexen-1-ol, (E)-2-hexen-1-ol, β-pinene, β-myrcene, (Z)-3-hexen-1-yl acetate, 1-hexyl acetate, 4-heptanone, (Z)-ocimene, linalool, linalool oxide, benzyl acetate, methyl salicylate, indole, β-caryophyllene, and (E)-β-farnesene. It was also reported by them that two pairs of insects caused a significantly stronger plant reaction.…”
Section: Discussionmentioning
confidence: 99%
“…Plants have developed various defense mechanisms to protect themselves from herbivores. When attacked by insects, many plant species release root exudates, which are mostly volatile compounds (VOCs) that affect the movement of their natural enemies [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 ]. Root-exudate-mediated chemotaxis plays a critical role in the multitrophic system of plants, herbivores, and their natural enemies.…”
Section: Introductionmentioning
confidence: 99%
“…These exudates function as semiochemicals, which directly influence both herbivores and their natural enemies. Some of these compounds are produced in both damaged and undamaged plants [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 ]. Different compounds are released when the plant is mechanically injured or when a particular herbivore species feeds on it [ 2 , 4 ].…”
Section: Introductionmentioning
confidence: 99%